2018
DOI: 10.1007/s11095-018-2453-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Virosomal RSV Vaccine Containing 3D-PHAD® Adjuvant: Formulation, Composition, and Long-Term Stability

Abstract: PurposeCharacterization of virosomes, in late stage preclinical development as vaccines for Respiratory Syncytial Virus (RSV), with a membrane-incorporated synthetic monophosphoryl lipid A, 3D-PHAD® adjuvant.MethodsVirosomes were initially formed by contacting a lipid film containing 3D-PHAD® with viral membranes solubilized with the short chain phospholipid DCPC, followed by dialysis, later by adding solubilized 3D-PHAD to viral membranes, or to preformed virosomes from DMSO.ResultsVirosomes formed from lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Moreover, our adjuvant selection was guided by the ability of TLR4 agonists to favour a tolerogenic response in Langerhans cells from human biopsies 12,13 and by the capacity of both TLR4 and TLR2 agonists to enhance AIT efficacy in asthma animal models 24,25 . In the context of our study, the choice of adjuvant was driven by the fact that 3D‐PHAD is a well‐defined molecule identical to one of the most active molecules present in 3‐desacyl MPLA and that 3D‐PHAD incorporation in virosomes showed promising data for feasibility and stability 26 . CL413 was also chosen as results presented by Laino et al 27 suggested efficacy in allergen immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our adjuvant selection was guided by the ability of TLR4 agonists to favour a tolerogenic response in Langerhans cells from human biopsies 12,13 and by the capacity of both TLR4 and TLR2 agonists to enhance AIT efficacy in asthma animal models 24,25 . In the context of our study, the choice of adjuvant was driven by the fact that 3D‐PHAD is a well‐defined molecule identical to one of the most active molecules present in 3‐desacyl MPLA and that 3D‐PHAD incorporation in virosomes showed promising data for feasibility and stability 26 . CL413 was also chosen as results presented by Laino et al 27 suggested efficacy in allergen immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 In the context of our study, the choice of adjuvant was driven by the fact that 3D-PHAD is a well-defined molecule identical to one of the most active molecules present in 3-desacyl MPLA and that 3D-PHAD incorporation in virosomes showed promising data for feasibility and stability. 26 CL413…”
Section: Vira-bet V 1 Cops Have a Better Safety Profilementioning
confidence: 99%
“…Furthermore, other enveloped viruses, such as hemagglutinating virus of Japan (HVJ), respiratory syncytial virus (RSV), and vesicular stomatitis virus (VSV), can be used to prepare virosomes [ 131 , 132 , 133 , 134 ]. In other cases, human hepatitis B virus-derived nanoparticles have been fused with liposomes, giving rise to virosome-like particles [ 131 , 134 , 135 ]. The lipoprotein inclusion results in structural stability of the virosomes and is responsible for disease targeting, cellular uptake, and endolysosomal escape following internalization of the carrier.…”
Section: Nano-biomimetic Drug Delivery Technologies As Potential Tmentioning
confidence: 99%
“…Generally, envelope glycoproteins derived from influenza virus, such as hemagglutinin (HA) and neuraminidase (NA), are reconstituted with liposomes to prepare virosomes for vaccination or delivery of different therapeutics (Daemen et al, 2005). Also, other enveloped viruses, such as hemagglutinating virus of Japan (HVJ), respiratory syncytial virus (RSV), and vesicular stomatitis virus (VSV), can be used to generate virosomes (Stegmann et al, 2010; Liu et al, 2015; Mohammadzadeh et al, 2016; Mohammadzadeh et al, 2017; Lederhofer et al, 2018). In other cases, human hepatitis B virus-derived nanoparticles were fused with liposomes, giving rise to virosome-like particles (Kaneda, 2012).…”
Section: Different Biomimetic Nanoparticles Developed For the Treatmementioning
confidence: 99%
“…Moreover, sterilizing immunity to RSV challenge was achieved by these adjuvanted virosomes in mice and cotton rats. Most recently, Lederhofer et al developed a virosomal RSV vaccine by incorporation of a lipid adjuvant 3-deacyl-phosphorylated hexa-acyl disaccharide (3D-PHAD) in viral membranes containing glycoproteins G and F (Lederhofer et al, 2018). In vivo immunization experiments in mice revealed effective production of RSV-specific neutralizing antibodies.…”
Section: Vaccines Based On Bioinspired Nanoparticlesmentioning
confidence: 99%